Fiscal Rules and the Sovereign Default Premium - Hatchondo, Juan Carlos (IMF Working Papers; Working Paper, 2012)
This paper finds optimal fiscal rule parameter values and measures the effects of imposing fiscal rules using a default model calibrated to an economy that in the absence of a fiscal rule pays a significant sovereign default premium. The paper also studies the case in which the government conducts a voluntary debt restructuring to capture the capital gains from the increase in its debt market value implied by a rule announcement. In addition, the paper shows how debt ceilings may reduce the procyclicality of fiscal policy and thus consumption volatility.